Implementasi Metode Cooperative Learning Pada Mata Pelajaran Fikih Dalam Meningkatkan Keaktifan Belajar Siswa di Kelas X-2 Mas Miftahussalam Medan - Afdiani Afdiani; Tumiran Tumiran; Sakban Lubis (Journal Of Dehasen Educational Review, 2026)
This study aims to determine the implementation of the cooperative learning method and student learning activity before and after the application of the method in the subject of Islamic Jurisprudence in class X-2 MAS Miftahussalam Medan. This study uses a qualitative method with a descriptive approach. The research subjects include the principal, Islamic Jurisprudence teachers, and class X-2 students. Data were collected through observation, interviews, and documentation. The data obtained were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the cooperative learning method has been carried out in accordance with the applicable learning stages and curriculum. This method is also able to increase student learning activity and understanding in the cognitive, affective, and psychomotor aspects, which is demonstrated through students' ability to practice prayer according to the correct requirements and pillars.